Effects of merger and acquisition announcement on shareholder value - Savolainen, Sami (My University, 2017)
The purpose of this thesis is to examine the effect of merger and acquisition announcements on shareholder value. This thesis analyzes the previous literature and execute an empirical study to find results to developed hypotheses that are related to shareholder value and deal performance. The sample of this thesis is gathered from January 2007 to August 2017 and includes mergers and acquisitions completed by Finnish listed companies during a determined time period. The empirical results of this thesis find that during a short-term the merger and acquisition announcement creates statistically significant abnormal returns of 1,61% and 2,67% during the event windows (-1, +1) and (-1, +30), respectively. In addition, the empirical study find that size of the acquirer, sector of the target and the nationality of the target has effect on the deal performance. However, only the sector of the target effects significantly on the shareholder value. In a long-term, the abnormal returns of the merger and acquisition announcement turned to negative, except for the combination portfolio, which includes transactions of domestic and different sector targets. However, the long-term combination portfolio’s result is statistically insignificant. According the empirical results, this thesis suggests that the management should select the target of the merger and acquisition in terms of their strategic goal. If management wants to maximize the shareholder value, they should find domestic target from a different sector of business.
Keywords: Merger and acquisition; shareholder value; abnormal return; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|